A New Approach to Cell Formation in Group Technology with Alternative Solutions - Abou-zeid, Mohammad; Boushaala, Amer; Madi, Haneya (Libyan Journal for Engineering Research, 2017)
The concept of group technology (GT) in design of manufacturing systems is explained. Achieving the highly appreciated benefits of applying GT mainly depends on proper design of manufacturing cells within a manufacturing system. As the ideal design of manufacturing cells is practically unattainable, research work aims at optimizing this process within a number of objectives. This paper categorizes and briefly introduces some of the previously published research work. Then, a proposed approach for design of manufacturing cells is introduced with the objective of minimizing the number of exceptional elements, needing processing in more than one cell, thus reducing the material handling needs between cells which reduces efficiency and increases costs. The mathematical model for this approach, based on the 0-1 incidence matrix of parts/machines, is explained. Five performance measures for the approaches of design of cells are applied to the proposed approach. Twelve previously published bench mark problems with eighty eight different solutions, based upon different approaches from literature, were used in the comparison and evaluation of the performance of the proposed approach/ model. The result of comparison indicated that the proposed approach gave better solutions in forty nine percent of the cases, with equal performance in the remaining cases. Thus, the proposed approach is a highly valued addition to the available approaches.